Grease film evolution in rolling elastohydrodynamic lubrication contacts - Xinming Li; Feng Guo; Gerhard Poll; Yang Fei; Ping Yang (Friction, 2020)
Abstract Although most rolling element bearings are grease lubricated, the underlying mechanisms of grease lubrication has not been fully explored. This study investigates grease film evolution with glass disc revolutions in rolling elastohydrodynamic lubrication (EHL) contacts. The evolution patterns of the grease films were highly related to the speed ranges and grease structures. The transference of thickener lumps, film thickness decay induced by starvation, and residual layer were recognized. The formation of an equilibrium film determined by the balance of lubricant loss and replenishment was analyzed. The primary mechanisms that dominate grease film formation in different lubricated contacts were clarified.